Representative bureaucracy in the Arab Gulf states. Issue 3 (8th April 2019) - Kemp, Linzi J.; Mathias, Megan; Raji, Maryam
Abstract : Purpose: The purpose of this paper is to apply the lens of representative bureaucracy (RB) to women's representation at management level in governments and government-owned companies in Arab Gulf states (AGS), and to consider the implications for government stability, legitimacy and performance. Design/methodology/approach: Data were analysed of the numbers of men and women in management positions (8, 936), of government and government-owned companies (846), for the six countries of the AGS. Analyses were conducted on the presence/absence of women in management for ten industry types. Findings: Governments and government-owned companies in the AGS were identified as hybrid (public/private) institutions. Women were found to be underrepresented at management levels in public sector bureaucracy; women clustered in a narrow range of industries; all countries returned a high result of zero female managers in these industries. Research limitations/implications: This research is limited by data collected from a single source, "Eikon", which is a commercial database. The implication of these results is a benchmark for future studies on women's representation at management level in governments and government-owned companies of Arab Gulf countries. Practical implications: The practical implication of this study is for concerted government intervention to address gender inequality in management of governments and government-owned companies across the AGS. Originality/value: This is the first study of RB in AGS and extends the theory of RB to a new geographical and cultural context. There is value in application of RB to government and government-owned companies as a regional form of hybrid public–private organisation.